(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The Tecoma stans Linn has been used for centuries in Indian medicine. It is a member of theBignoniaceae family and has several common names, including yellow bells, yellow elder, andtrumpet flower. There, it is considered a weed. T. stans has been shown to have chemical componentssuch as alkaloids, amino acids, phytosterols, monoterpenes, triterpenes, glycosides, phenols, tannins,saponins, and flavonoids, according to the research conducted on the plant. Leaves, roots, flowers,seeds, fruits, and bark, among other plant parts, have all been claimed to have therapeutic effects.Tecoma stans is a potent diuretic, vermifuge, antisyphilitic, stomach pain reliever, and tonic used fortreating diabetes, gastrointestinal issues, and the prevention of yeast infections. It was found duringpreliminary phytochemical screening and isolation that this plant included tannins, flavonoids, phenols,anthraquinones, glycosides, alkaloids, quinones, and trace amounts of saponins and amino acids. Anumber of diseases, including cancer, diabetes, and arthritis, have long been treated with the Tecomastans flower’s pharmacological benefits. Tecoma stans has been found to have a wide variety ofantibacterial, antifungal, cytotoxic, antimicrobial, antispasmodic, anti-inflammatory, andantiinflammatory activities. This plant extract has been found to contain gallic acid, a phenoliccompound that has anti-inflammatory properties. Similar results were observed with ethyl acetate andalcoholic extract of this plant on carrageenan-induced rat paw oedema. Pharmacological, phytochemical,and medicinal applications of Tecoma stans are discussed in this article.